M,H, B MENILIK HUBUNGAN BISNIS DALAM LINGKUP PEMILU DAN DEMOKASI INDONESIA: m, h, b - Hasanah, ulfia (UIR Law Review, 2024)
: Indonesia as a country that adheres to the ideology of constitutional democracy has provided opportunities for democracy through the provisions of article 96 of Law number 12 of 2011. That the community has the right and obligation to be involved in the formation of statutory regulations. The legal research method used in this paper is normative juridical research using a statutory approach and a conceptual approach. The development of the business world in the 2024 election is certainly very important because it determines the direction of the economy in the coming year. Because this is the moment to maintain economic stability so that Indonesia can succeed in becoming a high-income country. With elections, the business world can be more conducive and smooth. The position of democracy is related to the social system that supports it and the political system or regime that uses it. Apart from containing universal elements (common denominator), democracy also contains contextual contents that are inherent in certain social and political systems.